Hubungan Antara Kondisi Lingkungan Rumah dan Perilaku Masyarakat dengan Kejadian Filariasis di Kecamatan Pemayung Provinsi Jambi Tahun 2011 - Linggarjati Linggarjati; Sri Muryani; Abdul Hadi Kadarusno (Poltekkes Kemenkes Yogyakarta, 2012)
Filariasis is a chronic infectious disease which are caused by micro worms from filaroidea family.The disease worms is transmitted via mosquito vectorsand once a person catch the disease could result in permanent disability. Environment and human behavior are influential in spreading filariasis cases and the chains of transmission. The objectives of the study was to reveal the relationship between several independent variables, which consists of physical,biological, and social economic environment, and community behavior; and the incidence of filariasis in Kecamatan Pemayung, as one of endemic areas offilariasis in Jambi. The study employed case control study design. Each study groups comprised of 48 person. Observation and interview were the methodsof data collection. The results show that the factors which were proven as risk factors for filariasis are: education level (OR: 6,176; 95% CI: 1,643-23,216), occupation type (OR: 75,836; 95% CI: 4,52-1272,52), bed-net use (OR: 11,957; 95% CI: 3,712-38,515), out-door night activities (OR: 82,358; 95% CI: 4,91-1380,33), dressing habit (OR: 5,308; 95% CI: 1,082-26,040), the existence of watery plant (OR: 9,828; 95% CI: 2,668-36,206), the existence of animal reservoir (OR: 7,5; 95% CI: 2,016-27,901), and wall type (OR: 51,087; 95% CI: 6,51-400,853.